PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MEDIA GAMBAR DI MADRASAH IBTIDAIYAH - Alan Firdaus, Ade; Halidjah, Siti; Asmayani, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research is: "Is there an increase in student learning outcomes in Citizenship Education learning using image media in class V students of MIS Miftahul Ulum Sungai Kakap Kubu Raya Regency?" In general, this study aims to determine efforts to improve student learning outcomes in learning Education Citizenship uses the media for drawing in class V students of MIS Mi tahul Ulum Sungai Kakap, Kubu Raya Regency.The results obtained from the evaluation of Citizenship Education learning using image media in each cycle have increased. The average value in the first cycle was 65.23 and in the second cycle was 80.47. In the third cycle it was 94.76. This shows that the learning of Citizenship Education in Class V MIS Miftahul Ulum Sungai Kakap Kubu Raya can be increased and needs to be applied as a good learning, which can activate students' abilities. learning plans that are arranged at each stage of the cycle are in accordance with the criteria in preparing a good learning plan.Â Keywords: Image Media Citizenship Education, Learning Outcomes